Coexistence of an Unusual Form of Scabies and Lepromatous Leprosy. A case report - Barbosa Junior, Aryon de Almeida (1996)
Fundação Oswaldo Cruz, Centro de Pesquisas Gonçalo Moniz. Salvador, BA, Brasil